Crystal structure, Hirshfeld surface analysis and computational study of three 2-(4-arylthiazol-2-yl)isoindoline-1, 3-dione derivatives. Issue 1 (24th July 2022) - Ghabbour, Hazem A.; Fahim, Asmaa M.; Abu El-Enin, Mohammed A.; Al-Rashood, Sara T.; Abdel-Aziz, Hatem A.
Abstract: In these studies, we investigated the importance of isoindoline in pharmacological evaluation, so we studied the crystal structure, packing, Hirshfeld analysis and computational calculations of 2-(4-arylthiazol-2-yl)isoindoline-1, 3-dione derivatives 4a–c . All single crystal structures of these isoindoline-1, 3-dione were shown monoclinic system; P21/n space group and their net diploe moment 2.20, 3.73, 2.02 Debye, respectively. Furthermore, Hirshfeld surface analysis was useful technique for visualization and analyze the intermolecular interaction between atoms in molecule, therefore, the isoindoline derivatives 4a–c showed different contacts were mostly in H….H range (24.4%–36.5%), O….H range (8.7%–121.1%), S……H range (4.5%–5.6%) and C….H range (5.4–10.6%); respectively, and the isoindoline 4c showed higher intermolecular interaction dur to presence of two OCH3 groups. These single crystal structures of dione derivatives were comparable with theoretical studies utilized DFT/6-311(G)d, p basis set and determination their physical descriptors, MEP, HOMO-LUMO band energy gap and charge distribution. Moreover, the correlation studies of the 1HNMR spectral analysis between experimental and theoretical and they were excellent fitted with each other's.